Black bear hunting : expert strategies for success - Lewis, Gary; Van Tassell, Lee, 1956- (Chanhassen, Minn. : Creative Pub. International, 2007)
"This illustrated reference provides proven strategies on all techniques for hunting black bears in North America-from trip planning to game care in the field. Index included"--Provided by publisher.
Includes index.
Keywords: Black bear hunting